The Influence of low-temperature cold shock saturated water on the permeability characteristics of coal body and experimental study on permeability enhancement - Ke WANG; Hao YUAN; Hongwei LIU; Yanlong RONG (Meikuang Anquan)
In the development of coalbed methane (CBM), due to the generally low permeability of coal beds, effective permeability enhancement technology is needed to improve the extraction efficiency of CBM. Among them, low-temperature fracturing and permeability enhancement technology has been widely studied and applied. In this paper, we simulate the low-temperature environment in actual mining by applying low-temperature cold impact water saturation treatment to the coal body, in order to investigate the mechanical properties and seepage law of the coal body saturated with cold impact water at different temperature conditions. Negative pressure water-saturated device is used to saturate the specimen, after the specimen is completely saturated with water, it is put into the high and low temperature test chamber, and different specimens are impacted at room temperature, 0 ℃, −20 ℃ and −40 ℃, respectively. After the cold shock treatment of water-saturated specimens was completed, a triaxial percolation meter was used to carry out percolation test and triaxial compression test. The test results show that: cold shock treatment of water-saturated specimens will cause damage to the specimen, the development and expansion of internal cracks in the coal body, the specimen compressive strength decreases, and the permeability increases. And with the decrease of cold impact temperature, the permeability of the specimen gradually increases. The initial permeability of the specimen impacted at −40 ℃ was the largest, which increased by 202.9% compared with the normal temperature specimen.